Impact of Delayed Admission to the Intensive Care Unit from the Emergency Department upon Sepsis Outcomes and Sepsis Protocol Compliance - Michael Agustin; Lori Lyn Price; Augustine Andoh-Duku; Peter LaCamera (Critical Care Research and Practice)
Rationale. The impact of emergency department length of stay (EDLOS) upon sepsis outcomes needs clarification. We sought to better understand the relationship between EDLOS and both outcomes and protocol compliance in sepsis. Methods. We performed a retrospective observational study of septic patients admitted to the ICU from the ED between January 2012 and December 2015 in a single tertiary care teaching hospital. 287 patients with severe sepsis and septic shock were included. Study population was divided into patients with EDLOS < 6 hrs (early admission) versus ≥6 hours (delayed admission). We assessed the impact of EDLOS on hospital mortality, compliance with sepsis protocol, and resuscitation. Statistical significance was determined by chi-square test. Results. Of the 287 septic ED patients, 137 (47%) were admitted to the ICU in <6 hours. There was no significant in-hospital mortality difference between early and delayed admissions (p=0.68). Both groups have similar compliance with the 3-hour protocol (p=0.77). There was no significant difference in achieving optimal resuscitation within 12 hours (p=0.35). Conclusion. We found that clinical outcomes were not significantly different between early and delayed ICU admissions. Additionally, EDLOS did not impact compliance with the sepsis protocol with the exception of repeat lactate draw.